Conjugacy of Cartan subalgebras in EALAs with a non-fgc centreless core - Chernousov, V. (2017)
We establish the conjugacy of Cartan subalgebras for extended affine Lie algebras whose centreless core is “of type A”, i.e., ℓ×ℓ-matrices over a quantum torus Q whose trace lies in the commutator space of Q. This settles the last outstanding part of the conjugacy problem for Extended Affine Lie Algebras that remained open.